Countermovement Mobilization and State Raids on Minority Religious Communities - Wright, Stuart A. (Journal for the scientific study of religion, 2018)
An ongoing study of government raids on minority religious communities in 19 Western-style democracies over seven-plus decades shows a dramatic increase in raids beginning in the 1990s. Two distinct and related patterns are found to explain this escalation in frequency. Both patterns involved countermovement mobilization by coalitions of oppositional groups that effectively framed new or nontraditional religious movements (NRMs) as threats to their own members and the larger society, thereby prompting state actions of social control. The patterns are distinguished by a new relationship of countermovement actors to the state. In one pattern, we found the development of a transnational network forging a common collective action frame, movement ideology, and organizational strategy. Seizing political opportunities in the wake of increasing concerns regarding child endangerment, countermovement actors targeted NRMs as harbingers of child abuse and pressed authorities to take action. In the second pattern, we found a concentration of raids in one country (France). Here, the oppositional networks were not simply third-party interest groups but were fully integrated into the state apparatus, hence awarded power and given extraordinary influence. Consequently, state raids increased exponentially. The study also provides five years of new data from a previous report examining their impact on the larger set of findings and identifying new trends.